1983
DOI: 10.1111/j.1365-2125.1983.tb01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of combined vasodilation and beta‐adrenoceptor blockade with prizidilol on renal function.

Abstract: 1 The effects of a single oral dose of 600 mg of prizidilol on renal function were studied 5 to 6 h after dosing in six normal subjects and eight patients with essential hypertension. 2 Mean arterial blood pressure was reduced to 92% of the control value in normal subjects and to 75% in hypertensive patients. Heart rate increased slightly. 3 In normal subjects, effective renal plasma flow was increased to 107% of control values while glomerular filtration rate (83%), filtration fraction (79%), sodium (84%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…It is tempting to speculate that carvedilol, when given acutely, reduces the GFR by interfering with the compensatory autoregulatory constriction of the efferent arteriole, thus producing an acute decrease in glomerular perfusion pressure. It is noteworthy that prizidilol, a non-selective [3-blocker with vasodilating properties [30] that has been withdrawn from study because of side effects, has a definite renal vasodilatory effect and also reduces the GFR and FF after acute administration [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that carvedilol, when given acutely, reduces the GFR by interfering with the compensatory autoregulatory constriction of the efferent arteriole, thus producing an acute decrease in glomerular perfusion pressure. It is noteworthy that prizidilol, a non-selective [3-blocker with vasodilating properties [30] that has been withdrawn from study because of side effects, has a definite renal vasodilatory effect and also reduces the GFR and FF after acute administration [31].…”
Section: Discussionmentioning
confidence: 99%
“…The nonselective 13-adrenoceptor blockers, propranolol (Danesh et al, 1984) and nadolol (O'Callaghan et al, 1983), have been reported to reduce ERBF during short term oral administration as has the vasodilator Padrenoceptor blocker, prizidolol (Andersen et al, 1985). Another study of nadolol showed a significant increase in ERBF (Boehringer et al, 1983). Acebutolol, timolol, penbutolol and bevantolol have been reported as having no significant effect on GFR or ERBF (Solimon et al, 1986;Valvo et al, 1984; Van der Meiracker et al, 1988; Van der Meulen et al, 1986).…”
Section: Discussionmentioning
confidence: 96%
“…The prizidilol induced increase in renal perfusion, which takes place without change in cardiac output and fluid volumes (Lund-Johansen & Omvik, 1982), can probably be attributed to a selective renal vasodilation which is maintained beyond the acute administration of the drug (Boehringer et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The drug, in the long term, induces a favourable haemodynamic pattern in that it lowers blood pressure levels without modifying heart rate and cardiac output both at rest and during exercise (Lund-Johansen & Omvik, 1982). On the other hand, the acute administration of the drug has been reported to increase renal perfusion, but to depress glomerular filtration rate (Boehringer et al, 1983 Titration was effected until normalization of BP (<95 mm Hg diastolic BP (Korotkoff phase 5) after 5-min lying) unless important side effects appeared or the ceiling dose of 480 mg/day of propranolol and 800 mg/day of prizidilol was reached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation